Implementation of Fuzzy Logic to Regulate Water Quality in Maintaining the Aquascape Ecosystem - Muhammad Fajarudin; Handika Saputra Harahap; Irmansyah; Muhamad Al Habsy; Fardiana Yunita; Inna Novianty; Nanda Octavia; Ivan De Nerol (Batrisya Education, 2024)
Aquascape is an artificial aquarium ecosystem that is increasingly popular, considering the high cost of creating and maintaining an aquascape. Several aspects need to be considered in maintaining an aquascape, namely maintaining water quality. To know the water quality, it is necessary to periodically check the aquascape manually and carry out maintenance, therefore knowledge is needed to regulate and maintain the water quality in the aquascape. This research aims to implement fuzzy logic as a water quality control system in aquascape maintenance. The research method includes collecting data from the literature as well as developing a fuzzy logic model to identify and control water quality such as pH and temperature. The output of the system developed is a water quality control device with the categories